Evaluating Pre-Service Teaching Practice for Online and Distance Education Students in Pakistan: Evaluation of Teaching Practice - Ahmed Abdullah, Nauman; Sultana Mirza, Munawar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
In addition to conventional modes, teacher education programs in Pakistan are also offered through online and distance education. Teaching practice is a significant component of pre-service teacher education programs. Assessing the quality of teaching practice for pre-service student teachers is important, as these modules train the prospective teachers for their professional teaching careers. Virtual University of Pakistan (VU), an online university, offers pre-service teacher education programs. This research is an investigation into the learning opportunities and practices of VU student teachers in their teaching practice modules. Students enrolled in different teacher education programs served as the population of this study. Those in the fall 2018 semester who were enrolled in teaching practice modules were selected as a sample. Data sources included lesson plans prepared, lessons delivered, administrative and co-curricular duties performed by the students, as well as evaluation reports by supervisors, cooperating teachers, and school principals. There were improvements in the student teachers’ lesson plan formation and their overall learning. Data obtained through personal visits by VU faculty was used to verify and assess actual classroom teaching. Lack of regular attendance and punctuality by student teachers was observed as a result. Internal review of the VU system as it relates to the teaching practice modules was conducted to address any shortcomings in the course(s), its procedures, and its controls. Recommendations for improving the system, such as grading the modules, peer-assessment, and orientation workshops for student teachers are provided, as well as suggestions for developments in the teaching practice modules themselves.